(untitled) (Fiep Bulletin - online, 2014)
The objective of this study was to verify in athlete of judo of the masculine sex the physiological and metabolic variable during a training session. The athletes had age between 18 - 34 years old, being all pertaining a have equipped participant of the open games of the Paraná in the year of 2007. The sample was constituted by 10 athletes, who had in average 14,5 years of practical of the modality. The sanguineous lactate concentration, cardiac frequency (CF), and the IPE had been collected as parameters of effort intensity, during the Handoris (combats). We evidence that the accumulation of sanguineous lactate has great relation with the index of effort perception (during the combats how much lesser the concentration of lactate, minor would be the subjective scale of effort demonstrated for the athlete). The gotten results demonstrate high sanguineous lactate concentrations during the training, with 12,5 peak (mmol/l-1), and also raised answers of cardiac frequency, reaching 102% of the CF max. for the age. Knowing of the importance of the income and performance of the athletes and that sanguineous lactate is closer to the victory or defeat of judoka suggests that the periodic training in judo can use the tactical, physical training mainly (with weights) and the aerobic organism, that would assist in the reduction of the concentration of sanguineous lactate.